1992
DOI: 10.1002/pro.5560010611
|View full text |Cite
|
Sign up to set email alerts
|

Reversible dissociation and unfolding of the dimeric protein thymidylate synthase

Abstract: Conditions for in vitro unfolding and refolding of dimeric thymidylate synthase from Lactobacillus casei were found. Ultraviolet difference and circular dichroism spectra showed that the enzyme was completely unfolded at concentrations of urea over 5.5 M. As measured by restoration of enzyme activity, refolding was accomplished when 0.5 M potassium chloride was included in the refolding mixture. Recombination of subunits from catalytically inactive mutant homodimers to form an active hybrid dimer was achieved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0

Year Published

1993
1993
2013
2013

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 16 publications
(12 reference statements)
3
27
0
Order By: Relevance
“…Assuming that subunit exchange is involved in the restoration of TS activity, there would be only one cysteine containing active site in the resulting dimer, suggesting that only one complete active site is necessary to achieve full TS activity. When the extent of reactivation was measured by the urea denaturation-renaturation procedure of Perry et al (1992) that was used to restore activity to comparable mutant mixtures of L. casei TS , only half the E. coli wild-type activity was obtained, which is similar to what these investigators found.…”
Section: Restoration Of Activity To Inactive Mutantssupporting
confidence: 81%
“…Assuming that subunit exchange is involved in the restoration of TS activity, there would be only one cysteine containing active site in the resulting dimer, suggesting that only one complete active site is necessary to achieve full TS activity. When the extent of reactivation was measured by the urea denaturation-renaturation procedure of Perry et al (1992) that was used to restore activity to comparable mutant mixtures of L. casei TS , only half the E. coli wild-type activity was obtained, which is similar to what these investigators found.…”
Section: Restoration Of Activity To Inactive Mutantssupporting
confidence: 81%
“…The sensitivity of enzyme activity to subtle structural changes in a protein molecule makes measuring this property a useful and widely used functional probe to monitor protein unfolding (Herold and Kirschner, 1990;Perry et al, 1992;Kwon et al, 1993;Zhuang et al, 1994). The sensitivity of enzyme activity to subtle structural changes in a protein molecule makes measuring this property a useful and widely used functional probe to monitor protein unfolding (Herold and Kirschner, 1990;Perry et al, 1992;Kwon et al, 1993;Zhuang et al, 1994).…”
Section: Methodsmentioning
confidence: 99%
“…Up to 100 p L of each refolding reaction was assayed for TS activity in a total reaction volume of 1 mL. These conditions of unfolding/refolding and assay were optimized for L. casei TS (Perry et al, 1992).…”
Section: Methodsmentioning
confidence: 99%